EXPLORING THE EFFECT OF AUTONOMY AND PSYCHOLOGICAL WELLBEING: A COMPREHENSIVE ANALYSIS AMONG IIUM STUDENTS - Diaa Musa Diab Aljuneidi; Rodrigue Ancelot Harvey Fontaine; Ashurov Sharofiddin (Journal of Islamic Management Studies, 2024)
This study examines the influence of autonomy on the psychological well-being of 289 undergraduate students from the Kulliyyah of Economics and Management Sciences at the International Islamic University Malaysia. Employing the psychological well-being (PWB) scale for autonomy, regression tests demonstrate positive effects on psychological well-being. Key findings indicate a significant effect between autonomy and enhanced psychological well-being among students. The implications of these results suggest the importance of fostering autonomy in educational and personal development initiatives for university students. Future research might want to explore whether there are Islamic concepts in the Quran and the Sunnah that are similar to autonomy.